Semirigid fixed bridge management with nonvital abutment and narrowed space - Ira Tanti; Delivia (Indonesian Journal of Prosthodontic, 2025)
The prevalence of partial edentulism in adults underscores the increasing demand for tooth replacement options. Fixed partial dentures (FPDs) are widely accepted for this purpose. FPD success hinges on factors such as abutment condition, retainer, connector type, pontic design, and edentulous span. A five-unit fixed bridge with a pier abutment requires a non-rigid connector to enhance prosthetic longevity. Moreover, narrowed spaces require more attention. Analysis and diagnostic wax-up are needed for treatment planning. This case presenting the management of a five-unit semirigid fixed bridge with a non-vital pier abutment and narrow space using diagnostic wax-ups. A 62-year-old woman presented with a missing right mandibular first premolar and first molar, with the right mandibular canine and second molar serving as terminal abutments, and a non-vital second premolar serving as a pier abutment. The space between the canine and non-vital second premolar is narrower than normal. Analysis and diagnostic wax-up were done to ensure the space is enough and to avoid excessive reduction, mainly the canine, as it is a vital tooth. The non-vital pier abutment, which has been endodontically treated before, was strengthened with a fiber post. Continued with tooth preparation and fabrication of a five-unit porcelain fused to metal semi-rigid fixed bridge. The design of FPD plays an important role in the success of FPDs. The edentulous span and non-vital pier abutments require more attention; also, non-rigid connectors act as stress breakers to maintain the longevity of all components of FPDs. Keywords: fixed partial denture, non-rigid connector, pier abutment, non-vital abutment